Kích thích trí tuệ của quản lý và sự sáng tạo của cấp dưới: Vai trò của điều chỉnh nhiệm vụ và tự tin sáng tạo - Phan Quốc, Tấn; Phạm Tô Thục, Hân; Lê Công, Thuận; Trần Ngọc Phương, Anh (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2026)
Although supervisor intellectual stimulation affects subordinate creativity, the relationship is remains inconsistent. Therefore, the purpose of this study is to explore and test the mediating role of task crafting and the moderating role of creative self-efficacy to gain a deeper understanding of this relationship. Based on the ability-motivation-opportunity framework, this study addresses the inconsistent relationship between supervisor intellectual stimulation and subordinate creativity by testing the mediating role of task crafting and the moderating role of creative self-efficacy. This study employed SEM to test the hypotheses. The results show that task crafting mediates the relationship between supervisor intellectual stimulation and subordinate creativity. This study is one of the first to provide evidence that task crafting serves as a mediating mechanism linking the effect of supervisor intellectual stimulation on subordinate creativity. Furthermore, creative self-efficacy positively reinforces this relationship. The results indicate that the interaction between creative self-efficacy and supervisor intellectual stimulation helps employees achieve higher levels of creative performance.